Enhancing Procurement Quality Performance through the Improvement of a Quality Management System - Pradana, Hasta Dwi (Program Pascasarjana STIE Amkop Makassar, 2023)
The aim of this research is to develop a Quality Management System (QMS) for construction procurement in order to enhance contractors' performance. The successful implementation of construction work is crucial for the financial and operational performance of an institution. However, delays and disruptions often occur in construction projects due to low-quality work. To address this issue, this study utilized a literature review, questionnaire survey, and statistical analysis to develop a QMS for the procurement process of construction services. The results indicate that the QMS has the potential to enhance the performance of contractors and reduce the frequency of project delays. This study contributes to the field of construction work in institutions, and its findings have practical implications for improving the quality of construction work. Keywords: Quality Management System, Procurement, Construction Service, Contractor Performance